Odpowiedzi

2009-10-30T19:58:00+01:00
A) a - [ a - ( 1 - a ) ]
b) - x - [ - ( 1 - x ) - ( x - 1 ) ]
c) x - [ y - ( x - y ) - x - ( y - x ) ]
d) 1 - a - [ 1 - ( a - 1 ) - 2a - ( 1 - 3a ) ]- a - 1

a) a - ( 2a-1) = -a +1
b) -x - (0) = -x -0
c) x - (y - x +y-x-y+x)= x -y+x-y+x+x-y= 4x- 3y
d) 1-a-(1-a+1-2a-1+3a)-a-1= 1-a-1+a-1+2a+1-3a-a-1=-1 -a
2009-10-30T21:01:36+01:00
A) a - [ a - ( 1 - a ) ]
b) - x - [ - ( 1 - x ) - ( x - 1 ) ]
c) x - [ y - ( x - y ) - x - ( y - x ) ]
d) 1 - a - [ 1 - ( a - 1 ) - 2a - ( 1 - 3a ) ]- a - 1


a) a-[a-(1-a)]= a-(a-1+a)=a-a+1-a=1-a
b) -x-[-(1-x)-(x-1)]=-x-(1+x-x+1)=-x-1-x+x-1=-2-x
c) x - [ y - ( x - y ) - x - ( y - x ) ]= x-(y-x+y-x-y+x)=x-y+x-y+x+y-x=-y+2x
d) 1 - a - [ 1 - ( a - 1 ) - 2a - ( 1 - 3a ) ]- a - 1= 1-a-(1-a+1-2a-1+3a)=1-a-1+a-1+2a+1-3a=-a